2021
DOI: 10.1111/jfpp.15962
|View full text |Cite
|
Sign up to set email alerts
|

Air impingement to reduce thawing time of chicken fingers for food service

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Therefore, rais-ing surface heat transfer will not considerably improve the speed of freezing in thick products with low surface-tomass ratios, like joints of beef, but should increase the rate of freezing in thin foods with high surface-to-mass ratios, like burgers and pizzas. The effects of air impingement technology on the freezing and thawing of various products were examined by Bozzato et al (2021) and Góral & Domin (2005), and the results were compared with those of traditional freezing and thawing technologies. Less drip loss and greater nutrient retention were obtained in the products as a result of freezing and thawing processes using air impingement technology.…”
Section: Freezing Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, rais-ing surface heat transfer will not considerably improve the speed of freezing in thick products with low surface-tomass ratios, like joints of beef, but should increase the rate of freezing in thin foods with high surface-to-mass ratios, like burgers and pizzas. The effects of air impingement technology on the freezing and thawing of various products were examined by Bozzato et al (2021) and Góral & Domin (2005), and the results were compared with those of traditional freezing and thawing technologies. Less drip loss and greater nutrient retention were obtained in the products as a result of freezing and thawing processes using air impingement technology.…”
Section: Freezing Processmentioning
confidence: 99%
“…Low temperatures should be used for thawing processes involving air or water. Otherwise, microbial growth increases as the surface temperature rises above 5 • C. Thawing of food in the refrigerator requires long processing times (Bozzato et al, 2021). During thawing, the outside of the product is heated to the freezing point, and heat is transmitted to the product.…”
Section: Thawing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that nanomaterials were used as antioxidants, such as garlic nanoparticles (Abdelli et al, 2022) and date seed nanoparticles (Mostafa et al, 2022). There are few reports on chicken finger processing (Barutçu Mazi, 2009;Bozzato et al, 2021), and there is almost no information on chicken fingers containing nano-curcumin. Previous research has shown that, using natural preservatives, such as essential oil (Morsy et al, 2014) and oleaster leaf extract (Yaghoubi et al, 2023), in meat and chicken products improves microbial quality and shelf life.…”
Section: Introductionmentioning
confidence: 99%